2012
DOI: 10.2175/193864712811693272
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Thermal Hydrolysis Processes (CAMBI™ and EXELYS™) For Solids Pretreatmet Prior To Anaerobic Digestion

Abstract: Thermal hydrolysis is a sludge conditioning process applied to dewatered cake upstream of anaerobic digestion. The advantages of thermal hydrolysis are producing a Class A biosolids product, making residuals more digestible, and improving the dewatering characteristics of the resulting biosolids. Applying thermal hydrolysis to dewatered cake significantly reduces the viscosity allowing digesters to operate at much higher solids contents than conventional digesters significantly reducing volume requirements. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 5 publications
1
17
0
1
Order By: Relevance
“…It should be noted that cost analyses are geographically dependent and subsequently difficult to apply. Other studies have also shown costing data for thermal hydrolysis facilities (Abu-Orf & Goss, 2012;Childress et al, 2019;Goss, 2015;Jolly & Gillard, 2009;Loomis et al, 2016;Smith & Rus, 2019;Van Horn 2015;Williams, 2014) but some of these vary significantly even for projects of similar size and scope. The project in Medina, Ohio (Childress et al, 2019) cost $35 million USD for a facility with a design capacity of approximately 20 t DS/d.…”
Section: Capital Cost Of Thermal Hydrolysismentioning
confidence: 99%
“…It should be noted that cost analyses are geographically dependent and subsequently difficult to apply. Other studies have also shown costing data for thermal hydrolysis facilities (Abu-Orf & Goss, 2012;Childress et al, 2019;Goss, 2015;Jolly & Gillard, 2009;Loomis et al, 2016;Smith & Rus, 2019;Van Horn 2015;Williams, 2014) but some of these vary significantly even for projects of similar size and scope. The project in Medina, Ohio (Childress et al, 2019) cost $35 million USD for a facility with a design capacity of approximately 20 t DS/d.…”
Section: Capital Cost Of Thermal Hydrolysismentioning
confidence: 99%
“…Batch processes are well developed and several years of experience have been gained in the operation of these units. The future development of thermal hydrolysis of lignocellulosic biomass under continuous operation should be closely related to those designs that are currently being tested under industrial large scale for continuous thermal pre-treatment of sludge [ 12 , 178 ] operating at high solid content as the Cambi Solidstream ® (Cambi, Asker, Norway) process [ 179 ].…”
Section: Integrating Anaerobic Digestion Into a Green Energy Produmentioning
confidence: 99%
“…The first full-scale plant for sludge disintegration through the Cambi process was started in Hamar, Norway, in 1995 [ 11 ]. Since then, this company has installed several other plants worldwide [ 12 ]. Other commercial technologies include BioThelys™, which is a batch technology just as it is the Cambi TM Process (Cambi, Asker, Norway) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The former process uses a series of batch units and the latter uses a continuous plug flow reactor. Cambi process has more application history because it has been commercially available for a longer period; however, the Exelys process shows potential as it is reported to have a lower capital investment compared to the Cambi process [36].…”
Section: Full Scale Heat Application Case Studiesmentioning
confidence: 99%